Neurotoxicity in zebrafish exposed to carbon nanotubes: Effects on neurotransmitters levels and antioxidant system - Rocha, A. M. da (2019)
Given the increasing use of carbon nanotubes (CNT) in several industries and technological applications, it is essential to perform in vivo toxicological studies with these nanomaterials to evaluate their potential ecotoxicity. Dopamine (DA) and serotonin (5HT) are key neurotransmitters for brain functions and behavioral responses. Determination of DA and 5HT were performed in brain samples from zebrafish Danio rerio exposed i.p. to single-walled CNT (SWCNT), besides analyzing acetylcholinesterase (AChE) and ectonucleotidases activity, lipid peroxidation and total antioxidant capacity. Results showed that treatment with SWCNT increased between 3 and 6-fold the concentration of DA and 5HT (p < 0.05). Similarly, a significant reduction (p < 0.05) in AChE activity was observed in the brains of SWCNT exposed zebrafish when compared to the control groups. Cholinergic, serotonergic, and dopaminergic systems, through AChE activity and serotonin and dopamine levels, respectively were affected by SWCNT in the zebrafish brain. Alterations in these neurotransmitters can potentially affect several physiological and behavioral that they control.